Konstruksi Ring Bersih dari Sebarang Ring - Kartika Sari; Indah Emilia Wijayanti (Mathematics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2015)
The aims of this research was to construct a clean ring from any ring. The base on the fact that the endomorphism ring of every pure-injective module is clean, it was constructed a clean ring from any ring. So, the result of this research was it always could be constructed a clean ring from any ring.